Implementasi Konsep Matematika pada Metode ‘Aul dalam Pembagian Harta Warisan - Lutfiana, Fira Aini; Nurjanah; Sulastri, Yayu Laila; Fadilawati, Fani; Syakur, Novia Nurwasyi; Nurwahid, Eef Hidayat (Papanda, 2025)
The 'Aul method in Islamic inheritance law is used when the total portions assigned to heirs exceed 100%. Mathematics plays a crucial role in ensuring fair and Sharia-compliant distribution. This study, titled